Banyan Tree - Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
The title of the postcard is incorrect, the tree in the picture is a Ficus benjamina (Benjamin Tree or Weeping fig).
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Ficus benghalensis; Banyan tree--Trinidad and Tobago; Ficus benjamina; Weeping fig--Trinidad and Tobago; Ficus (Plants)--Trinidad and Tobago